2022
DOI: 10.1007/s40843-022-2099-9
|View full text |Cite
|
Sign up to set email alerts
|

MXene-mediated regulation of local electric field surrounding polyoxometalate nanoparticles for improved lithium storage

Abstract: Due to their capability of reversibly accepting multi lithium ions, polyoxometalates (POMs) have been widely regarded as promising candidates for electrochemical lithium storage. Nevertheless, the insulating nature of POMs hinders fast migration kinetics of lithium within the bulk of these materials. Herein, we propose the introduction of a local electric field surrounding the POM nanoparticles consisting of Mn and V where the concomitant Coulomb forces can accelerate the migration of lithium ions. After ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 64 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…A Keggin-type polyoxometalate (PMo 12 ) was first reported to be used as the anode material of LIBs in 2012, and it was found that each PMo 12 molecule reversibly transfers 24 electrons during the lithiation and delithiation processes . From then on, some smaller POMs, including PMo 12 , PMo 10 V 2 , PW 12 , , SiW 12 , Co 8 W 12 , and so on, which are combined with functional support materials, such as MXene, organic linkers, , MOFs, CNTs, , and GO, , were mainly reported for energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…A Keggin-type polyoxometalate (PMo 12 ) was first reported to be used as the anode material of LIBs in 2012, and it was found that each PMo 12 molecule reversibly transfers 24 electrons during the lithiation and delithiation processes . From then on, some smaller POMs, including PMo 12 , PMo 10 V 2 , PW 12 , , SiW 12 , Co 8 W 12 , and so on, which are combined with functional support materials, such as MXene, organic linkers, , MOFs, CNTs, , and GO, , were mainly reported for energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…Although the high-throughput computational screening contributes to a partial solution to this obstacle, the extremely-high computer configuration is inevitably needed, which largely restricts the wide use of this method. [8][9][10][11] To promote the large deployment of renewable energy, the key materials for EESC are supposed to offer a long duration. To determine this parameter experimentally is almost impossible, thus making an accurate prediction of the calendar life of these materials is strongly needed.…”
Section: Introductionmentioning
confidence: 99%
“…The search for key materials of EESC is generally realized via laborious and costly trial‐and‐error processes, which cannot meet the imminent requirement of “Carbon Neutrality.” Although the high‐throughput computational screening contributes to a partial solution to this obstacle, the extremely‐high computer configuration is inevitably needed, which largely restricts the wide use of this method 8–11 . To promote the large deployment of renewable energy, the key materials for EESC are supposed to offer a long duration.…”
Section: Introductionmentioning
confidence: 99%